Răspunsuri

2014-08-04T12:37:30+03:00
A) 3x-9 -8=20

3x-17=20

3x=20+17

3x=37

x=37/3

b)15-4x-4=10
11-4x=10

-4x =10-11

-4x= -1

4x=1

x=1/4

c)35/24: x=2 intregi 3/9

35/24 *1/x= 2 intregi 1/3

35/24 *1/x= 7/3

1/x=7/3 : 35/24

1/x= 7/3 *24/35

1/x=8/5

x=5/8

d)4x+5 =x+13

4x-x=13-5

3x=8

x= 8/3

e)11x+17= 2x+21

11x-2x=21-17

9x=4

x=4/9

f)7/18 +x =19/15   aducem la acelasi numitor

105 +270x= 342

270x= 342-105

270x= 237

x= 237/270

g)37/3 : {[11/4:(5/3 +15x/8)]*8/11+5/3 }=5

11/4: (5/3 +15x/8)*8/11 +5/3 =5 *37/3

11/4 :(5/3 +15x/8)*8/11+5/3 = 185/3

11/4 : (5/3 +15x/8)*8/11 =185/3 -5/3

11/4 :(5/3 +15x/8) *8/11 =180/3

11/4 :(5/3 +15x/8)=60 : 8/11

5/3 +15x/8 =60 * 11/8 * 11/4

5/3 +15x/8= 15* 121/8

5/3 +15x/8= 1815/8   aducem la acelasi numitor

40+ 45x= 5445

45x=5445-40

45x= 5405

x=5405/45=  1081/9